2019
DOI: 10.1007/s10508-019-1416-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Relationship Quality Across Different Types of Romantic Partners in Polyamorous and Monogamous Relationships

Abstract: Polyamory is the practice of having multiple emotionally-close relationships that may or may not be sexual. Research concerning polyamory has just begun to determine how relationships among partners in polyamorous arrangements may vary. Most of the research assessing perceptions of polyamorous partners has focused on primary-secondary configurations; however, non-hierarchical configurations exist, such as having multiple primary partners or having only non-primary partners. The current research is the first to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 54 publications
5
23
0
5
Order By: Relevance
“…SRB is a documented mental health problem in the alternative sexuality community [20], with existing literature highlighting mental health [21], stigma-associated emotions [13], and acquired capability [12] as risk factors. The present study employed relationship orientation (e.g., non-monogamy) [34,66], health inequity/marginalized identity [5,37], and PIP [50,58] to further investigate factors associated with SRB among members of the alternative sexuality community. As is discussed in the following sections, all three perspectives, plus known mental health and suicide exposure-related factors, added value in understanding SRB.…”
Section: Discussionmentioning
confidence: 99%
“…SRB is a documented mental health problem in the alternative sexuality community [20], with existing literature highlighting mental health [21], stigma-associated emotions [13], and acquired capability [12] as risk factors. The present study employed relationship orientation (e.g., non-monogamy) [34,66], health inequity/marginalized identity [5,37], and PIP [50,58] to further investigate factors associated with SRB among members of the alternative sexuality community. As is discussed in the following sections, all three perspectives, plus known mental health and suicide exposure-related factors, added value in understanding SRB.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of polyamory, romantic love and emotional closeness is often viewed as endless rather than limited to only one person (Moors et al, 2019). Polyamorous relationships are structured in a variety of ways, including one or two "primary" partners (often the focal or longest relationship partner) and additional "secondary" partner(s) (often referred to as hierarchical polyamory; Barker, 2005;Sheff and Tesene, 2015;Balzarini et al, 2019a). Polyamorous relationships may also take the form of triads (three person relationships), quads (four person relationships), or "V"s (Munson and Stelboum, 1999;Barker, 2005).…”
Section: Consensual Non-monogamy: Boundaries and Definitionsmentioning
confidence: 99%
“…Regarding the relationship that romantic love has with the type of affective sexual relationship practiced, some articles, especially qualitative studies, discuss a few types of non-hegemonic relationships in depth. However, few investigations delve into the possible similarities or differences between this type of relationship and traditional monogamous ones (Balzarini et al, 2019a , b ). In one of the first works on the subject of study, Klesse ( 2006 )—who interviewed non-heterosexual people in non-monogamous sexual relationships—found that polyamorous people constructed the term polyamory as a consensual non-monogamy, away from the principles of monogamy and romantic love.…”
Section: Research On Lovementioning
confidence: 99%
“…Thus, the studies presented suggest that consensual non-monogamous forms do not differ substantially from romantic forms and that they have also incorporated characteristics of the latter. According to the findings of Balzarini et al ( 2019a ) it would not be enough to compare consensual non-monogamous relationships with monogamous ones, as the different configurations of polyamorous relationships would influence the similarities and differences that might exist with monogamous relationships.…”
Section: Research On Lovementioning
confidence: 99%